Gambaran Persepsi Remaja tentang Triad Kesehatan Reproduksi Remaja dengan Teori Health Belief Model - Tjokorda Istri Rai Oktalia Andayani; Ni Made Dwi Purnamayanti; Ni Komang Yuni Rahyani (ProHealth Journal, 2025)
The Health Belief Model is an appropriate instrument for predicting adolescent health behavior. It provides an overview of the perception of internal factors, external factors and produces adolescent beliefs related to the KRR Triad. The purpose of the study was to determine the overview of adolescent perceptions of the KRR Triad with the Health Belief Model Theory at SMAN 1 Kuta. The type of research was descriptive. The sample size of 64 was taken by proportional random sampling, namely Grade XI students were divided into 12 classes, from each class a number of male and female students were taken, the instrument used was the Health Belief Model - Perceived Susceptibility (HMPBB) questionnaire with a total of 90 statements. The results showed negative perceptions in the perception of vulnerability as many as 61 people (95.3%), and perceptions of obstacles as many as 53 people (82.8%), positive perceptions in the perception of seriousness 57 people (89.1%), perceptions of benefits 42 people (65.6%), self-efficacy 41 people (64.1%), and cues to action 46 people (71.9%). Data collection was conducted on April 21, 2025, at SMA N 1 Kuta. The conclusion is that adolescents have a negative perception of the KRR triad in terms of perceived vulnerability and perceived barriers. Suggestions for KSPAN activities include using intervention strategies that involve active adolescent participation, interactive media, and peer-based approaches.